Paediatric Epilepsy: A Comprehensive Overview of Diagnosis, Treatment and Management - Sireesha, Vankodoth; Nikshitha, Manne; Nikitha, Sunkari; Ramya, Kaluvala; Rao, Tadikonda Rama (Indian Journal of Pharmacy Practice)
Seizures are characterized as a transient episode of symptoms arising from abnormal, excessive, or synchronized firing of brain neurons that is accompanied by sudden, involuntary skeletal muscle contractions. Among the most common neurological diseases in children, epilepsy is particularly prevalent during the first year of life. Premature birth, neurological comorbidity, positive family history, fever, infections, maternal alcohol misuse, maternal complications and smoking during pregnancy are among the risk factors associated with the beginning of seizures, particularly in children. Children’s neurological morbidity is primarily due by epilepsies. About 5 out of every 1,000 children will have epilepsy in any given year, while the average annually rates of new cases of the disorder being around 5-7 cases per 10,000 children from between the ages of one and fifteen. The prevention of epilepsy and seizures requires early diagnosis, treatment and specialized medical care. A comprehensive investigation that includes a detailed medical history, physical examination, and neuroimaging investigations is necessary for the diagnosis of epilepsy in children. Individualized treatment plans are developed for children with epilepsy, taking into account the child’s general health, underlying etiology, and seizure type and frequency. Antiepileptic medications (AEDs) are commonly used as first-line therapy based on the type of seizure. In some instances, alternative therapies like the ketogenic diet therapy may be taken into consideration when patients are not responding to medication.
Keywords: Seizures; Premature birth; Epilepsy; Neurological morbidity; Neuroimaging; Antiepileptic drugs; Ketogenic Diet